Multidentate Azo Dye Complexes of Dioxouranium(VI), Thorium(IV) and Cerium(IV). - MOHANTA , HRUDANANDA; L. SAHOO, KANAKA (Asian Journal of Chemistry, 2010)
A series of complexes of dioxouranium(VI), thorium(IV) and cerium(IV) has been prepared using neutral 1-(2-pyridyl azo)-2-naphthol (PANH). The neutral ligand and not the anion of the azodye form the complexes. These complexes were characterised by IR, UV, conductivity and elemental analysis. The complexes formed have the composition [UO2(HL)2X2], where X = NO3–, CH3COO–, Cl–, I–, SCN– or 0.5 SO42–,[UO2L2], [Th(HL)2X4] where X = NO3–, I– or SCN– and [CeL3(HL)3].